Differential effects of speech situations on mothers’ and fathers’ infant-directed and dog-directed speech: An acoustic analysis - Gergely, Anna (Sci Rep, 2017)
There is growing evidence that dog-directed and infant-directed speech have similar acoustic characteristics, like high overall pitch, wide pitch range, and attention-getting devices. However, it is still unclear whether dog- and infant-directed speech have gender or context-dependent acoustic features. In the present study, we collected comparable infant-, dog-, and adult directed speech samples (IDS, DDS, and ADS) in four different speech situations (Storytelling, Task solving, Teaching, and Fixed sentences situations); we obtained the samples from parents whose infants were younger than 30 months of age and also had pet dog at home. We found that ADS was different from IDS and DDS, independently of the speakers’ gender and the given situation. Higher overall pitch in DDS than in IDS during free situations was also found. Our results show that both parents hyperarticulate their vowels when talking to children but not when addressing dogs: this result is consistent with the goal of hyperspeech in language tutoring. Mothers, however, exaggerate their vowels for their infants under 18 months more than fathers do. Our findings suggest that IDS and DDS have context-dependent features and support the notion that people adapt their prosodic features to the acoustic preferences and emotional needs of their audience.